Differential Associations between Guilt and Shame Proneness and Religious Coping Styles in a Diverse Sample of Young Adults - Ladis, Ilana (Journal of interpersonal violence, 2023)
Positive religious coping is linked with better mental health outcomes following physical and sexual abuse while negative religious coping is associated with poorer outcomes. Religious coping styles may be linked with dispositional tendencies to experience guilt or shame. This study compared the associations between guilt and shame proneness and religious coping styles and tested whether abuse history moderated these relationships. We conducted a cross-sectional study with 425 college students (n = 145 with physical and/or sexual abuse history, n = 280 with no abuse history). Participants completed questionnaires assessing positive and negative religious coping style, as well as two dimensions of guilt proneness and shame proneness. Structural equation models were fitted to examine associations between guilt proneness and shame proneness, and positive and negative religious coping, respectively, accounting for abuse history as a binary moderator. Across the full sample, positive religious coping was positively associated with guilt repair (i.e., the tendency to engage in reparative behaviors following one’s wrongdoing), guilt negative behavior evaluation (i.e., the tendency to feel bad about how one acted in a given scenario), and shame withdrawal (i.e., the tendency to try and avoid unpleasant situations in which one has done something wrong), and negatively associated with shame negative self-evaluation (i.e., the tendency to make internal, negative self-attributions about one’s wrongdoing). Negative religious coping was positively associated with shame withdrawal and, for participants with no abuse history, shame negative self-evaluation. Results suggest that positive religious coping is more closely related to guilt proneness, and negative religious coping to shame proneness. Additional research with longitudinal designs and more defined abuse history subgroups is needed.